Use of Natural Biomaterials in Tissue Regeneration - Yari-Ilkhchi, Ayda (IntechOpen, 2025)
Tissue engineering is a strong method for developing functional alternatives for regenerative medicine that plays a vital role in the therapy of patients. Effective tissue regeneration requires the creation of biologically active substrates with optimum physicochemical, mechanical, and biological properties. Biopolymers with superior biocompatibility and biodegradability are ideal for tissue engineering and regenerative medicine. Depending on the target tissue, several kinds of natural-driven biopolymers, including chitosan, hyaluronic acid, gelatin, and collagen, can be created to perform a variety of particular roles. In this chapter, we review the numerous types of biopolymers used to repair and regenerate tissues, such as skin, heart, nerve, bone, and cartilage, as well as their interactions with certain cells and tissues. In addition, particular cellular mechanisms are being investigated in tissue regeneration in order to clarify the effects of biopolymers on modulating cellular systems, considering their benefits and challenges. However, further advances are required to overcome the limitations and challenges associated with the use of biopolymers in tissue regeneration.